"استجابة نباتات الذرة الصفراء مقساة البذار للإجهاد الملحي" - خليل, نديم; زيدان, علي; العلي, عبد العزيز; جزدان, عمر; طعمة, الهام (Latakia University Journal -Biological Sciences Series, 2013)
يهدف البحث إلى دراسة أثر كل من التقسية الملحية لبذور الذرة الصفراء (صنف غوطة 82) وأثر نوعية مياه الري في إنتاجية النباتات ومحتوى أنسجتها من عناصر Cl, Na, K، فنقعت مجموعة من بذور الذرة الصفراء في مياه نهر الفرات العذبة ((EC:1.03 dS.m-1، ومجموعة أخرى في مياه صرف زراعي (EC: 5.89 dS.m-1) لمدة (12) ساعة، ثم جففت بذور المجموعتين وزرعت في قطع تجريبية مساحتها (15م2) لكل مكرر، ورويت النباتات خلال فصل النمو بأربع أنواع مختلفة من مياه الري (100% مياه فرات، 50% مياه فرات + 50% مياه صرف ، 33% مياه فرات + 67 مياه صرف، 100% مياه صرف). قدرت العناصرCl, Na, K في النبات ووزن الـ (1000) حبة والإنتاج الصافي من الحبوب لكل مكرر وكل معاملة بالكغ.هـ.-1. أظهرت النتائج أنه يمكن الوصول إلى إنتاج حوالي (3) طن من الحبوب للهكتار، باستعمال مياه صرف زراعي فقط في الري الذي يمكن اعتباره مقبولاً في ظروف المناطق الجافة. كما إن التقسية الملحية للبذور ساهمت في زيادة الإنتاج الصافي من الحبوب بنسبة (32.80%)، وهذه النسبة تعدُّ مرضية تحت ظروف منطقة التجربة. In order to study the effect of prime treatment (salt hardening) on maize seeds (variety Ghouta 82) and type of irrigation water on the plant response to salt stress through the effect on the productivity and the plant tissue contents Cl, Na and K. Maize seeds were soaked in Euphrates fresh water (EC:1.03 dS.m-1), or in agricultural drainage water (EC: 5.89 dS.m-1) for (12) hours, the seeds therefore were dried and planted in plots of (15 m2) for each replicate and then irrigated with four different types of water; (100 % Euphrates water, 50% Euph. water + 50% agri. drain. water, 33 % Euph. water + 67 % agri. drain. water, and 100% agri. drain. water) during the growing season. K, Na, and Cl in plants were determinated, 1000 grains weight, and grain yield production were estimated in kg.h-1 for each replicate and treatment. The results showed that, it is possible to have 3 tons of grain / hectare by irrigation with agricultural drainage water, which is acceptable, under semi-arid conditions. Salt hardening of maize seeds increased seed yield by (32.80%), which is considered satisfactory under the experimental conditions.